A numerical study on effects stress and displacement on abdominal adhesions during palpations to be used in tactile sensing - Nur Thaqifah Mohamed Taha (2017)
Adhesion is a major problem in today’s society with is being the root cause of many serious diseases such as small bowel obstruction. Millions of dollars are wasted annually to help and cure the diseases with adhesion as its main culprit. With such a widespread effect on the world, we still have no way of non-intrusively defining an adhesion in a patient. Now, with tactile sensing gaining followers by the minute due to its ability to use changes in deformation and stress to map out a lesion. It has since been used for the detection of lumps in breasts for breast cancer. In our study, the ability of using tactile sensing to detect adhesion was investigated. In SolidWorks was utilized to model our abdomen and adhesion before uploading it into ANSYS. ANSYS was used to simulate the changes in deformation and stress when it undergoes three different studies: 1. Varying size of adhesion 2. Varying position of adhesion and 3. Varying pressure or force applied on abdomen. From this study, tactile graphs were attained where the maximal stress and the percentage change in stress can be calculated and analysed. From the simulations, tactile sensing was concluded to be highly capable of detecting adhesions as the stress graphs on the surface can be obtained. Maximal stress differences were more apparent in adhesions along the linea alba as compared to adhesions closer to the longitudinal edge of the abdomen. It was found that the percentage change in stress in the point 1, point 2, point 3 and point 4 are 2-5%, 5-10%, up to 20% and up to 30% respectively. Additionally, the change in maximal stress and maximal vertical deformation affected by increase in point load had a linear relationship. Moreover, this method was able to define the length of adhesion in that plane. This study can act as a stepping stone to further studies to develop a tactile sensor used to detect adhesion.